2020
DOI: 10.1109/lra.2020.3015452
|View full text |Cite
|
Sign up to set email alerts
|

An Ionic Polymer Metal Composite (IPMC)-Driven Linear Peristaltic Microfluidic Pump

Abstract: Microfluidic devices and micro-pumps are increasingly necessitated in many fields ranging from untethered soft robots, to pharmaceutical and biomedical technology. While realization of such devices is limited by miniaturization constraints of conventional actuators, these restrictions can be resolved by using smart material transducers instead. This paper proposes and investigates the first ionic polymer metal composite (IPMC) actuator-driven linear peristaltic pump. With the aim of designing a monolithic devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Accordingly, various pumps based on smart materials have been developed. These smart materials include shape memory alloys (SMA) [5][6][7] , piezoelectric ceramics (PZT) 8,9 , dielectric elastomers (DE) [10][11][12][13] , polyvinylidene fluoride (PVDF) 14 , ionic polymer metal composites (IPMC) [15][16][17][18] , and conductive polymers (CP) 19 .As a smart material, polyvinyl chloride (PVC) gel exhibits promising features for pumps. PVC gels are normally synthesized by mixing PVC resins and liquid plasticizes (e.g., dibutyl adipate), and they typically have a sheet-like form [20][21][22] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, various pumps based on smart materials have been developed. These smart materials include shape memory alloys (SMA) [5][6][7] , piezoelectric ceramics (PZT) 8,9 , dielectric elastomers (DE) [10][11][12][13] , polyvinylidene fluoride (PVDF) 14 , ionic polymer metal composites (IPMC) [15][16][17][18] , and conductive polymers (CP) 19 .As a smart material, polyvinyl chloride (PVC) gel exhibits promising features for pumps. PVC gels are normally synthesized by mixing PVC resins and liquid plasticizes (e.g., dibutyl adipate), and they typically have a sheet-like form [20][21][22] .…”
mentioning
confidence: 99%
“…Accordingly, various pumps based on smart materials have been developed. These smart materials include shape memory alloys (SMA) [5][6][7] , piezoelectric ceramics (PZT) 8,9 , dielectric elastomers (DE) [10][11][12][13] , polyvinylidene fluoride (PVDF) 14 , ionic polymer metal composites (IPMC) [15][16][17][18] , and conductive polymers (CP) 19 .…”
mentioning
confidence: 99%
“…In addition to the engineering applications, IPMCs have also been proposed for medical devices or biomedical applications because of their unique stimulus-response actuation performance. [134][135][136][137][138] Guo et al proposed the application of an ionic actuator as a guide for microcatheter with two degrees of freedom in the front section as servo actuators, and the results showed that IPMC was applicable to intracavity operations. [139] Lu et al prepared a MDOF IPMC active catheter by an electrode splitting technique, aiming to obtain the deformation capability in 3D space.…”
Section: Medical Devicesmentioning
confidence: 99%
“…[140] Sideris et al designed an IPMC-operated linear peristaltic pump, which could achieve a pumping rate of 669 pL s −1 (open pump). [137] Moreover, a capsule-like robot that can be used for endoscope diagnosis was proposed, using IPMCs as actuators. [138] Interventional catheters, peristaltic pumps, and capsule robots are key research areas for IPMC medical applications.…”
Section: Medical Devicesmentioning
confidence: 99%
“…A cantilever IPMC is used as a driver to increase the deformation of the valve, thereby improving the performance of the micropump. Wang et al integrated an inner petalshaped IPMC as an actuating diaphragm into micropump [Figure 11H], improving the performance of micropump [178] . Besides, some other configurations for micropumps have also been proposed.…”
Section: Medical Treatment Devicesmentioning
confidence: 99%